Women’s employment and marital stability: the role of the context - Styrc, Marta; Matysiak, Anna (Studia Demograficzne, 2012)
A discussion of the effects of partners’ labour force participation on marital stability has been part of the demographic debate for several decades. While theorists generally agree that men’s employment has a stabilizing effect on marriage, there is considerable controversy about the effects of women’s involvement in the labour market on marital stability. This debate has centred on several models and arguments. The most recent contributions have underlined the role of the context in moderating the relationship in question, and our study aims to contribute to this debate. We use the case of Poland, a country that underwent rapid and profound changes in its economic, institutional, and socio-cultural settings. Using GGS- PL data, we estimated a hazard regression of marital disruption, separately for women and men. The effects of employment status were allowed to vary by calendar time in order to determine how the relationship between women’s economic activity and marital stability was affected by the transformation of the labour market; the reassignment of responsibility for an individual’s welfare among the state, the family, and the market; the change in institutional support for families; and the liberalisation of the gender roles. Our empirical study showed that, after the onset of the economic transformation, working women became significantly more likely to divorce than women who did not have a job. This finding implies that the economic transformation led to a substantial increase in women’s dependence on their partners, and made it much more difficult for non-working women to exit unhappy marriages. This conclusion is further corroborated by our finding that, relative to working women, the disruption risk among women on maternity and parental leave declined over time. As expected, men’s employment was found to stabilise marriages both prior to and after 1989.